Green compression strength of tin mine tailing sand for green sand casting mould - Abdullah, Azhar; Sulaiman, Shamsuddin; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar; Vijayaram, Thoguluva Raghavan (Universiti Putra Malaysia Press, 2013)
Tailing sand is the residue mineral from tin extraction that contains between 94% and 99.5% silica, which can be used as moulding sand. It is found in abundance in the Kinta Valley in the state of Perak, Malaysia. Adequate water content and clay in moulding sand are important factors for better strength and casting quality of products made from tailing sand. Samples of tailing sand were investigated according to the American Foundrymen Society (AFS) standard. Cylindrical test pieces of Ø50 mm×50 mm in height from various sand-water ratios were compacted by applying three ramming blows of 6666g each using a Ridsdale-Dietert metric standard rammer. The specimens were tested for green compression strength using a Ridsdale-Dietert universal sand strength machine. Before the tests were conducted, moisture content of the tailing sand was measured using a moisture analyser. A mixture bonded with 8% clay possesses higher green compression strength compared to samples bonded with 4% clay. The results also show that in order to achieve maximum green compression strength, the optimum allowable moisture content for mixtures bonded with 8% clay is ranged between 3.75 and 6.5% and for mixtures bonded with 4% clay is 3-5.5%.